Geomagnetic control of equatorial plasma bubble activity modeled by the TIEGCM with Kp. Issue 15 (1st August 2014) - Carter, B. A.; Retterer, J. M.; Yizengaw, E.; Groves, K.; Caton, R.; McNamara, L.; Bridgwood, C.; Francis, M.; Terkildsen, M.; Norman, R.; Zhang, K.
Abstract Describing the day‐to‐day variability of Equatorial Plasma Bubble (EPB) occurrence remains a significant challenge. In this study we use the Thermosphere‐Ionosphere Electrodynamics General Circulation Model (TIEGCM), driven by solar (F10.7) and geomagnetic (Kp) activity indices, to study daily variations of the linear Rayleigh‐Taylor (R‐T) instability growth rate in relation to the measured scintillation strength at five longitudinally distributed stations. For locations characterized by generally favorable conditions for EPB growth (i.e., within the scintillation season for that location), we find that the TIEGCM is capable of identifying days when EPB development, determined from the calculated R‐T growth rate, is suppressed as a result of geomagnetic activity. Both observed and modeled upward plasma drifts indicate that the prereversal enhancement scales linearly with Kp from several hours prior, from which it is concluded that even small Kp changes cause significant variations in daily EPB growth.